2014
DOI: 10.1007/s10815-014-0376-z
|View full text |Cite
|
Sign up to set email alerts
|

An infertile 45,X male with a SRY-bearing chromosome 13: a clinical case report and literature review

Abstract: Purpose Patients with a karyotype of 45,X (monosomy X) normally display a female phenotype. However, in some rare cases, monosomy X is associated with maleness. Here we describe a case of a male with a 45,X karyotype and primary infertility, which prompted molecular investigation of the sexdetermination gene SRY. Methods Karyotyping was performed by GTG-banded chromosome analysis. The presence and location of SRY was investigated using PCR and FISH, respectively. Results PCR confirmed the presence of the SRY g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Translocation of the SRY gene can also be tested by FISH in individuals with 46,XX testicular or ovotesticular DSD [Laino et al, 2014;Baetens et al, 2017]. However, rare locations of the translocated gene can also be uncovered [Peng et al, 2015]. Deletions and amplifications >50 kb can be identified for known chromosomal regions only since FISH probes are designed to be complementary to a known target DNA sequence which is subsequently indicated by the presence or absence of a fluorescent signal.…”
Section: Diagnostic Technologies In Geneticsmentioning
confidence: 99%
“…Translocation of the SRY gene can also be tested by FISH in individuals with 46,XX testicular or ovotesticular DSD [Laino et al, 2014;Baetens et al, 2017]. However, rare locations of the translocated gene can also be uncovered [Peng et al, 2015]. Deletions and amplifications >50 kb can be identified for known chromosomal regions only since FISH probes are designed to be complementary to a known target DNA sequence which is subsequently indicated by the presence or absence of a fluorescent signal.…”
Section: Diagnostic Technologies In Geneticsmentioning
confidence: 99%
“…Men with 45,X karyotype normally display a female phenotype. They are infertile and display azoospermia [65]. The underlying mechanism for this abnormality is related to the absence of the genes on the long arm of the Y chromosome which are responsible for spermatogenesis.…”
Section: X Male Syndromementioning
confidence: 99%
“…Since the distal part of the euchromatic long Y arm (Yq11) is lost, these patients have an unbalanced karyotype [52]. Multiple studies showed normal secondary sexual characteristics and normal reproductive hormone levels, but small testes, azoospermia, and germinal aplasia in patients with a 45x Karyotype [65].…”
Section: X Male Syndromementioning
confidence: 99%